Penerapan Nilai-nilai Kearifan Lokal Tapanuli Bagian Selatan dalam Mewujudkan Dakwah Damai dan Toleran Di Tengah Arus Ideologi Transnasional - Ali Amran (IAIN Padangsidimpuan, 2018)
There are values and norms In every society like the form of customs such as the Southern Tapanuli Society, the community must follow the norm in carrying out its activities in various areas of life, the application of customs value or local wisdom is very important in supporting and realizing peace and tolerant dakwah in the middle of the flow developed transnational ideology and also to realize a peaceful and tolerant society in the diversity of the nation.